Aminopeptidase O Protein mediates the association between Lachnospiraceae and appendicular lean mass - Gao, Bingjun; Zhou, Zhonghua; Chen, Junfei; Zhang, Shengling; Jin, Shaobin; Yang, Weiwei; Lei, Yinghan; Wang, Kunyao; Li, Jinxu; Zhuang, Yan (Frontiers in Microbiology, 2024)
Objective: Investigating the causal relationship between Lachnospiraceae and Appendicular lean mass (ALM) and identifying and quantifying the role of Aminopeptidase O Protein (AOPEP) as a potential mediator.The summary statistics data of gut microbiota composition from the largest available genome-wide association study(GWAS) meta-analysis conducted by the MiBioGen Consortium(n=13,266). Appendicular lean mass data were obtained from the UK-Biobank (n=450,243). We conducted bidirectional two-sample Mendelian randomization(MR) analysis using summary-level data from GWAS to investigate the causal relationship between Lachnospiraceae and ALM. Additionally, we employed a drug-targeted MR approach to assess the causal relationship between AOPEP and ALM. Finally, a two-step MR was employed to quantitatively estimate the proportion of the effect of Lachnospiraceae on ALM that is mediated by AOPEP. Cochran's Q statistic was used to quantify heterogeneity among instrumental variable estimates.In the MR analysis, it was found that an increase in genetically predicted Lachnospiraceae(OR=1.031, 95% CI [1.011-1.051], P=0.002) is associated with an increase in ALM. There is no strong evidence to suggest that genetically predicted ALM has an impact on Lachnospiraceae genus (OR=1.437, 95% CI [0.785-2.269], P=0.239). The proportion of genetically predicted Lachnospiraceae mediated by AOPEP was 34.2% (95%CI [1.3%-67.1%]).Our research reveals that increasing Lachnospiraceae abundance in the gut can directly enhance limb muscle mass and concurrently suppress AOPEP, consequently mitigating limb muscle loss. This supports the potential therapeutic modulation of gut microbiota for sarcopenia. Interventions such as drug treatments or microbiota transplantation, aimed at elevating Lachnospiraceae abundance and AOPEP inhibition, synergistically improve sarcopenia in the elderly, thereby enhancing the overall quality of life for older individuals.